Characterization of the curing agents used in epoxy resins with TG/FT-IR technique - Romão,Benedita M. V. (2006)
Samples of epoxy resin (EP) based on the diglycidyl ether of bisphenol A (DGEBA), cured with nadic methyl anhydride (NMA) and mercaptan (CAPCURE 3-800), or amine-phenol (CAPCURE EH-30), respectively, SE 4 and SE 5, were prepared in the stoichiometric ratio determined by the supplier. The curing behaviour of the epoxy systems SE 4 and SE 5 was followed by DSC (Differential Scanning Calorimetry). These SE and their ingredients were analyzed using FTIR transmission techniques (KBr pellets, pyrolysis without control and controlled pyrolysis-FT-IR, the CONTROLPIR/FT-IR) for characterizing the curing agents (CA). The temperature range used for samples pyrolysis was found from TG (thermogravimetry). Thus, the FT-IR bands of liquid pyrolysate obtained by CONTROLPIR/FT-IR were evaluated, in comparison to the reference spectrum of CA. The characterization of CA was also possible, by the analysis of such SE with the TG/FT-IR technique.